1996
DOI: 10.1007/bf00311781
|View full text |Cite
|
Sign up to set email alerts
|

Enhancement of portal blood flow by ursodesoxycholic acid in partially hepatectomized rats

Abstract: Portal venous flow (PVF) was examined after portal injection of ursodesoxycholic acid (URSO) in rats that were partially hepatectomized by either 40% or 66%. URSO (10 mg/kg per minute) was injected into the portal vein and was thereafter observed to increase PVF concomitantly with a fall in portal vein and was thereafter observed to increase PVF concomitantly with a fall in portal venous pressure (PVP) in control animals. The increase in PVF in response to URSO was dose-dependent. In hepatectomized rats, the P… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
3
0

Year Published

1996
1996
2000
2000

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 8 publications
0
3
0
Order By: Relevance
“…It has been shown that portal blood rates; when the ICG-K was lowered to below 0.06, flow evoked by PGE and ursodeoxycholic acid was in-these rates were increased (Table 4). This is in keepcreased by partial hepatectomy in anesthetized ani-ing with the view that the improvement in the ICG mals [14,15,19]. This may also be true of ICG.…”
Section: Table 3 Serum Liver Functional Parameters Before and After Omentioning
confidence: 99%
See 1 more Smart Citation
“…It has been shown that portal blood rates; when the ICG-K was lowered to below 0.06, flow evoked by PGE and ursodeoxycholic acid was in-these rates were increased (Table 4). This is in keepcreased by partial hepatectomy in anesthetized ani-ing with the view that the improvement in the ICG mals [14,15,19]. This may also be true of ICG.…”
Section: Table 3 Serum Liver Functional Parameters Before and After Omentioning
confidence: 99%
“…On the other hand, purpose of this study is to investigate whether PGE it has been shown that hepatectomy decreases the efinfluences the ICG disappearance rate in patients with fective concentration of vasodilative agents such as hepatic resection. Eleven patients with hepatic resec-PGE and ursodeoxycholic acid [14,15,19]. …”
mentioning
confidence: 99%
“…Both observations may be caused either by an improvement in the liver archi- tecture [19]with a decrease in portal venous outflow resistance or by an effect of UDCA on splanchnic hemodynamics. A limited number of small in vitro studies [20]as well as animal experiments [21, 22]suggested that UDCA has at least some direct vasodilative effect on the portal venous smooth musculature. In our study we could not observe a direct vasodilative effect of a chronic oral treatment of UDCA onthe portal venous system, although the gallbladder showed a considerable increase in fasting volume.…”
Section: Discussionmentioning
confidence: 99%